PENGARUH PENERAPAN PEMBELAJARAN WEB BASED LEARNING SOCIAL MEDIA DESIGN TERHADAP KOMPETENSI FISIKA SISWA KELAS X SMA NEGERI 1 KUBUNG SOLOK - Anofa Liona; Yenni Darvina; Pakhrur Razi (PILLAR OF PHYSICS EDUCATION, 2016)
Curriculum emphasizes student-centered learning process, teachers are required to guide and facilitate the students so that students are motivated to learn well in school and outside. In order to the learning process goes well we need a learning model that can support that learning. In this case web-based learning social media design can increase the activity of students in the learning process and improve good student interaction with teachers, classmates and the subject matter. That way the students can be expected to increase physical competence. The purposes of this research was to investigate the effect web based learning social media design to the competency of Physics students grade X at SMAN 1 Kubung Solok. Type of research was quasi experimental with randomized control group only design. The population in this research were the students grade X MIA SMAN I Kubung Solok who were registered in the 2014/2015 academic year. Sampling technique was Cluster Random sampling. There were three instruments in this research, those were test sheet of knowledge domain, observation sheet of attitude domain, and performance sheet of skill domain. Based on the data analysis could be presented the result of this research. First, the average value of students which use web based learning social media design  in knowledge domain, attitude domain, and skill domain were 87.52, 90.52, and 86.90 respectively. Second, the use of web based learning social media design has given significant effect toward Physics competency of students grade X SMAN 1 Kubung Solok at 0,05 signifacation level